Permintaan, Penawaran, dan Harga Perspektif Ibnu Khaldun - Husna Ni'matul Ulya (Justicia Islamica, 2015)
Ibn Khaldun is one of the famous economists in the history of Islamic thought, where he lived in the second period of the history of Islamic thought. In his book Muqaddimah, he describes many economic theories that are widely applied in modern economics, one of which is the theory of demand, supply and price. He agrees that the price is formed from the tug of war of supply and demand, while still considering other factors. In this case, Ibn Khaldun's theory has many similarities with modern economics, this may be due to many Western thinkers who adopted his thoughts, although Ibn Khaldun's theory tends to lead more to empirical evidence than to be poured into statements.